Establishing a social work model for China's rural vitalisation strategy. Issue 3 (2nd September 2021) - Boddie, Stephanie Clintonia; Jiao, Ruoshui; Webster, Michael; Zhao, Qianwei; Hodge, David R.
ABSTRACT: This article documents a social work education model from an emerging collaboration among scholars in China, Aotearoa New Zealand, and the United States to adapt Western and Indigenous Māori theories and practices to the Chinese context. To advance this model, we map our process by 1) outlining the challenges in China and comparing them to those in Aotearoa New Zealand and the United States; 2) summarising the social work history and culture in each country; 3) outlining universal elements and examples of social work practices; and 4) identifying ways in which these countries can innovate and collaborate to support the development of a new social work education model for China's rural vitalisation strategy. This model adopts the Māori Whare Tapa Wha (English: "four cornerstones of health") as a living expression of inter-ethnic health practice applied to social work practice in Aotearoa New Zealand.